Flexural strengthening of reinforced concrete beams using precast SIFCON thin plate - Abdul Aziz, Farah Nora Aznieta; Elliott, Kim S. (2008)
The use of Slurry Infiltrated Fibre Reinforced Concrete (SIFCON), a composite cementitious material reinforced with a high density of short steel fibres, has been investigated as an externally bonded strengthened material on reinforced concrete beams. Literature has shown that it has been successfully applied for strengthening application such as bridge deck, pavement and beam-column joint. However due to difficulty to produce it on-site and to control fibre orientation during the manufacturing process its application has been limited. Therefore this research had studied the use of SIFCON material as prefabricated thin (25 mm) precast plate for strengthening application. These precast SIFCON thin plates were bonded on sides and bottom surfaces of the beam using low viscosity epoxy resin of less than 5 mm thickness. Six reinforced concrete beams of (experimentally convenient) 100 mm x 200 mm x 1376 mm span were pre-loaded before being strengthened with the precast SIFCON thin plates. Results show that, compared to an unstrengthened control beam, the flexural strength of the strengthened beams increased by up to 88.7 %, whilst the elastic bending stiffness increased by 40%.